IMPLEMENTASI DAN PENGGUNAAN SISTEM INFORMASI ADMINISTRASI SURAT MENYURAT BERBASIS WEB - Muhammad Nurdina; Lulus Dewi Amirakhim (Lembaga Pengembangan Kinerja Dosen, 2021)
The Upper Silat Sub-District Head Office is precisely at Jl. Jend. Sudirman No. 08, is an organization of the Kapuas Hulu Regency Government. Which organization is run by the Government apparatus. The sub-district is the sub-district head's working area as a regional apparatus headed by the sub-district head who is under and responsible to the regent who has the main task of assisting the regent in the administration of the government, development and community life development fields. Where at the moment the procedure applied to archiving incoming and outgoing mails in the Kalinyamat, Sumatra Utara District starts from reception, manufacture, storage, documentation, to letter verification, all done conventionally which results in the letters in Kalinyamat, Sumatra Utara District not being managed with well, it is very difficult when looking for old documents because they have to look one by one. Objectives to accelerate the process of filing incoming and outgoing mail in the Kalinyamat, Sumatra Utara District starting from receiving, making, storing, documenting, and verifying letters. For research methods used are: Data collection, system analysis, system design and system implementation. The results of this study are expected to accelerate the process of archiving correspondence in the Kalinyamat, Sumatra Utara District